Role of Health Literacy in Self-Reported Musculoskeletal Disorders. (18th August 2015) - Hill, Catherine L.; Appleton, Sarah L.; Black, Julie; Hoon, Elizabeth; Rudd, Rima E.; Adams, Robert J.; Gill, Tiffany
Abstract : Self-report of musculoskeletal conditions is often used to estimate population prevalence and to determine disease burden and influence policy. However, self-report of certain musculoskeletal conditions is frequently inaccurate, suggesting inadequate communication to the patient of their diagnosis. The aim of this study is to determine the association between functional health literacy (FHL) and self-reported musculoskeletal conditions in a representative population survey. FHL was measured using Newest Vital Sign in 2824 randomly selected adults. Participants also self-reported medically diagnosed arthritis, gout, and osteoporosis. Multiple logistic regression was adjusted for age and sex. The prevalence of self-reported arthritis, gout, and osteoporosis was 25.2%, 4.9%, and 5.6%, respectively. The prevalence of those at risk for inadequate FHL was 24.0% and high likelihood of inadequate FHL was 21.0%. However, over 50% of respondents with arthritis or gout had at risk/inadequate FHL, increasing to 70% of those self-reporting osteoporosis. After adjustment for age and sex, respondents in the arthritis subgroup of "don't know" and self-reported osteoporosis were significantly more likely to have inadequate FHL than the general population. This study indicates a substantial burden of low health literacy amongst people with musculoskeletal disease. This has implications for provider-patient communication, individual healthcare, population estimates of musculoskeletal disease, and impact of public health messages.